Effectiveness of Linkage to Care and Prevention Interventions Following HIV Self-Testing: A Global Systematic Review and Meta-analysis - Adeagbo, Oluwafemi Atanda; Badru, Oluwaseun Abdulganiyu; Nkfusai, Claude Ngwayu; Bain, Luchuo Engelbert (AIDS and behavior, 2024)
Over 38.4 million people were living with HIV globally in 2021. The HIV continuum includes HIV testing, diagnosis, linkage to combined antiretroviral therapy (cART), and retention in care. An important innovation in the HIV care continuum is HIV self-testing. There is a paucity of evidence regarding the effectiveness of interventions aimed at linking self-testers to care and prevention, including pre-exposure prophylaxis (PrEP). To bridge this gap, we carried out a global systematic review and meta-analysis to ascertain the effectiveness of interventions post-HIV self-testing regarding: (1) linkage to care or ART, (2) linkage to PrEP, and (3) the impact of HIV self-test (HIVST) interventions on sexual behaviors. We searched PubMed, Web of Science, SCOPUS, Cochrane Library, CINAHL Plus (EBSCO), MEDLINE (Ovid), Google Scholar, and ResearchGate. We included only published randomized controlled trials (RCTs) and quasi-experiment that compared HIVST to the standard of care (SoC). Studies with sufficient data were aggregated using meta-analysis on RevMan 5.4 at a 95% confidence interval. Cochrane’s Q test was used to assess heterogeneity between the studies, while Higgins and Thompson’s I 2 was used to quantify heterogeneity. Subgroup analyses were conducted to identify the source of heterogeneity. Of the 2669 articles obtained from the databases, only 15 studies were eligible for this review, and eight were included in the final meta-analysis. Overall, linkage to care was similar between the HIVST arm and SoC (effect size: 0.92 [0.45–1.86]; I 2 : 51%; p: 0.04). In the population subgroup analysis, female sex workers (FSWs) in the HIVST arm were significantly linked to care compared to the SoC arm (effect size: 0.53 [0.30–0.94]; I 2 : 0%; p: 0.41). HIVST interventions did not significantly improve ART initiation in the HIVST arm compared to the SoC arm (effect size: 0.90 [0.45–1.79]; I 2 : 74%; p: < 0.001). We found that more male partners of women living with HIV in the SoC arm initiated PrEP compared to partners in the HIVST arm. The meta-analysis showed no difference between the HIVST and SoC arm regarding the number of clients (effect size: − 0.66 [1.35–0.02]; I 2 : 64%; p: 0.09) and non-clients FSWs see per night (effect size: − 1.45 [− 1.45 to 1.38]; I 2 : 93%; p: < 0.001). HIVST did not reduce the use of condoms during insertive or receptive condomless anal intercourse among MSM. HIVST does not improve linkage to care in the general population but does among FSWs. HIVST intervention does not improve linkage to ART nor significantly stimulate healthy sexual behaviors among priority groups. The only RCT that linked HIVST to PrEP found that PrEP uptake was higher among partners of women living with HIV in the SoC arm than in the HIVST arm. More RCTs among priority groups are needed, and the influence of HIVST on PrEP uptake should be further investigated.